2015
DOI: 10.1161/strokeaha.114.007330
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cell Death Is Reduced With Cooling by 3.5°C to 5°C but Increased With Cooling by 8.5°C in a Piglet Asphyxia Model

Abstract: Background and Purpose In infants with moderate to severe neonatal encephalopathy, whole body cooling to 33-34°C for 72 hours is standard care with a number needed to treat to prevent one adverse outcome of 6-7. The precise brain temperature providing optimal neuroprotection is unknown. Methods After a quantified global cerebral hypoxic-ischemic insult, 28 piglets aged <24h were randomized (each group n=7) to: (i) normothermia (38.5°C throughout), or whole-body cooling 2-26 h post-insult to (ii) 35°C, (iii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 13 publications
4
78
0
4
Order By: Relevance
“…This may explain our observation of a significantly lower body temperature at 2-3.5 h in the hypothermia + dexmedetomdine group, although this was not below the target TH range. We have previously shown that the depth of hypothermia is critical for its efficacy in this model [48] .…”
Section: Discussionmentioning
confidence: 82%
“…This may explain our observation of a significantly lower body temperature at 2-3.5 h in the hypothermia + dexmedetomdine group, although this was not below the target TH range. We have previously shown that the depth of hypothermia is critical for its efficacy in this model [48] .…”
Section: Discussionmentioning
confidence: 82%
“…In other cases, animal studies indicated futility, which was later borne out in clinical studies. For example, animal studies suggested the futility of deeper cooling following perinatal HI;13 this was seen in the randomised controlled trial of deeper and longer therapeutic hypothermia for NE, which was subsequently stopped due to safety concerns14 There are calls for more systematic reviews of animal studies and higher standards of research conduct and reporting 10…”
Section: Factors To Consider For Translation Of Animal Studies To Humansmentioning
confidence: 99%
“…The brain needs to be cooled to limit neurologic complications in patients during sudden strokes and heart attacks. For cases where hypothermia cannot be applied, local cooling of the brain prevents neurological damage that may subsequently take place like restrictions in memory, speech, and movement [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%